2017
DOI: 10.1371/journal.pone.0171495
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation therapy and fracture risk in Chinese patients with prostate carcinoma

Abstract: ObjectiveAndrogen deprivation therapy (ADT) increases fracture risk in men with carcinoma of the prostate, but little is known about the fracture risk for different types of ADT. We studied the fracture risk amongst Chinese patients with carcinoma of the prostate prescribed different ADT regimens.Subjects and methodsThis was a single-centered observational study that involved 741 patients with carcinoma of the prostate from January 2001 to December 2011.ResultsAfter a median follow-up of 5 years, 71.7% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The pathophysiology of bone fracture in men with prostate cancer is that ADT suppresses not only 95 percent of testosterone level but also reduces approximately 80 percent of endogenous estrogen level, causing bone turnover, resorption and eventually loss in BMD ( 23 , 34 ). The association between ADT and clinical fracture risk has been confirmed by several retrospective and population-based studies ( 6 8 , 17 , 24 , 25 ). The odds ratios were slightly different for different patient populations studied.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The pathophysiology of bone fracture in men with prostate cancer is that ADT suppresses not only 95 percent of testosterone level but also reduces approximately 80 percent of endogenous estrogen level, causing bone turnover, resorption and eventually loss in BMD ( 23 , 34 ). The association between ADT and clinical fracture risk has been confirmed by several retrospective and population-based studies ( 6 8 , 17 , 24 , 25 ). The odds ratios were slightly different for different patient populations studied.…”
Section: Discussionmentioning
confidence: 67%
“…Whereas, the rate of fracture associated with ADT was 1.3-fold in non-metastatic prostate cancer patients and by 1.5-fold risk in metastatic patients in a United States cohort from the SEER-Medicare database (17). In a Chinese population, a single center study reported that use of ADT was associated with a 3.6-fold higher risk of having any fracture (25).…”
Section: Discussionmentioning
confidence: 96%
“…Of these 141 studies, 41 were excluded because they were conference abstracts/papers; 30 were excluded because they were review articles; 12 were excluded because they were editorials, comments, letters, short surveys, or replies; 24 were excluded because they had ineligible study designs or effect sizes or different dosing regimens; 1 was excluded because it was a published meta-analysis including the risks of fracture, osteoporosis, and osteopenia with ADT (Serpa Neto et al, 2010). Finally, 16 full-text studies (n 519,168 individuals) (López et al, 2005;Shahinian et al, 2005;Smith et al, 2005;Smith et al, 2006;Alibhai et al, 2010;Beebe-Dimmer et al, 2012;Shao et al, 2013;Kaipia et al, 2014;Morgans et al, 2014;Teoh et al, 2015;Wang et al, 2015;Wu et al, 2015;Wallis et al, 2016;Lee et al, 2017;Nguyen et al, 2018;Wallander et al, 2019) were included.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Three were conducted in Europe [Sweden (Wallander et al, 2019), Finland (Kaipia et al, 2014), and Spain (López et al, 2005)], 8 in the United States (Shahinian et al, 2005;Smith et al, 2005;Smith et al, 2006;Beebe-Dimmer et al, 2012;Shao et al, 2013;Morgans et al, 2014;Wallis et al, 2016;Nguyen et al, 2018), 1 in Canada (Alibhai et al, 2010), and 4 in Asia [Taiwan (Wu et al, 2015), New Zealand (Wang et al, 2015), and China (Teoh et al, 2015;Lee et al, 2017)]. Thirteen studies assessed the risk of any fracture (López et al, 2005;Shahinian et al, 2005;Smith et al, 2005;Smith et al, 2006;Alibhai et al, 2010;Shao et al, 2013;Kaipia et al, 2014;Morgans et al, 2014;Teoh et al, 2015;Wu et al, 2015;Lee et al, 2017;Nguyen et al, 2018;Wallander et al, 2019), 5 assessed the risk of fracture requiring hospitalization (Shahinian et al, 2005;Beebe-Dimmer et al, 2012;Wang et al, 2015;Wallis et al, 2016;Lee et al, 2017), and 3 assessed the risk of hip fracture (Smith et al, 2006;Kaipia et al, 2014;Wallander et al, 2019). The number of study participants ranged from 201,797 in the Surveillance, Epidemiology, and End Results (SEER) program to 452 in a single-hospital study from China.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…The rate of bone loss in PCa patients on ADT seems to be comparable to the overall rate of bone loss in post-menopausal women [22]. The association of ADT and osteoporosis is clinically relevant for fragility fracture risk, a fact that has been proven by observational studies that report an increased risk for any fracture [23] with the necessity for different osteosynthesis methods [24,25], due to subjacent affected bone mineralization, for all types of ADT [26]. Since patients with PCa have a higher mortality risk caused by PCa-related and non-related events [27], adding the risk of morbidity and mortality associated REV.CHIM.(Bucharest)♦69♦No.…”
mentioning
confidence: 99%